Factors of Organizational Performance in High-Growth Smes: an Investigation From Turkish Manufacturing Industry - Gönül, Ebubeki̇r (MEF Üniversitesi, 2023)
Bu çalışma, Türk imalat sanayinde hızlı büyüyen küçük ve orta ölçekli işletmelerin (KOBİ) performansını etkileyen faktörleri incelemeyi amaçlamaktadır. Bu amaçla, Türkiye'de faaliyet gösteren KOBİ'lerin organizasyonel, finansal ve kaynak yönetimi performanslarını etkileyen ortak başarı ve başarısızlık faktörlerinin araştırılmasına yönelik ampirik bir araştırma yapılmıştır. İmalat sanayi, sağladığı pek çok fayda ve ülkenin büyüme ve kalkınmasında hayati bir rol oynaması nedeniyle Türk ekonomisi için çok önemli bir sektördür. İmalat sektörü, Türkiye'nin Gayri Safi Yurtiçi Hasılasının (GSYİH) önemli bir kısmından sorumludur ve milyonlarca işçiye iş sağlayarak işsizliği azaltır ve ekonomik büyümeyi destekler. Ayrıca imalat sanayi, ülkenin ticaret dengesinin ve döviz rezervlerinin anahtarı olan Türkiye'nin ihracat gelirlerine de önemli bir katkı sağlıyor. Üreticiler, ürünlerini ve süreçlerini iyileştirmek için araştırma ve geliştirmeye yatırım yaptıklarından, sektör teknolojik gelişmeyi de tetikliyor. Ayrıca imalat sanayinin büyümesi, özellikle daha kırsal ve az gelişmiş bölgelerde bölgesel kalkınmanın desteklenmesinde ve bölgesel eşitsizliklerin azaltılmasında önemli bir faktördür. Sonuç olarak, imalat sanayii Türkiye için büyük önem taşımaktadır ve bu sanayinin sürekli büyümesi ve gelişmesi için devletin ve diğer paydaşların desteğine ihtiyaç duyulmaktadır.

This study aims to examine the factors that affect performance of high-growth small and medium sized enterprises (SMEs) in Turkish manufacturing industry. For that objective, an empirical research is conducted for investigating the common success and failure factors influencing the organizational, financial, and resource management performance of SMEs operating in Türkiye. The manufacturing industry is a crucial sector for Turkish economy, as it provides a multitude of benefits and plays a vital role in the country's growth and development. The manufacturing sector is responsible for a significant portion of Turkey's Gross Domestic Product (GDP) and provides jobs to millions of workers, reducing unemployment and fostering economic growth. Additionally, the manufacturing industry is a major contributor to Turkey's export earnings, which is the key for the country's balance of trade and foreign currency reserves. The sector also drives technological development, as manufacturers invest in research and development to improve their products and processes. Furthermore, the growth of the manufacturing industry is an important factor in supporting regional development and reducing regional disparities, particularly in the more rural and less developed areas. In conclusion, the manufacturing industry is of utmost importance for Turkey, and its continued growth and development requires support from the government and other stakeholders.
Türk üretim endüstrisi'nde hızlı büyüyen KOBİlerin organizasyon performans faktörleri
Keywords: İşletme; Business Administration